PENINGKATAN KEMAMPUAN MENGENAL HURUF HIJAIYAH PADA ANAK USIA 5 TAHUN MENGGUNAKAN METODE TILAWATI DI RA NURUL IMAN TAHUN PELAJARAN 2025/2026 - Suhatimi; Wijaya Adi Putra; Nurhafit Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to improve children's ability to recognize Hijaiyah letters, which are an important foundation in learning to read the Qur'an. Many early childhood children still experience difficulties in differentiating the form, pronouncing, and mentioning Hijaiyah letters because the learning provided has not fully matched their developmental characteristics. The ability to recognize Hijaiyah letters is the first step in the child's religious process. The introduction of Hijaiyah letters not only trains the child's language skills, but also instills spiritual values from an early age. However, in reality, there are still many early childhood children, especially in RA institutions, who have difficulty recognizing the shapes and sounds of Hijaiyah letters. This can be seen from the initial observations made at RA Nurul Iman, which showed that there were 10 children out of 15 children in group A, aged 5 years, who were unable to differentiate some Hijaiyah letters that have similar shapes, such as   ب (ba), ت (ta), and ث (tsa)  ج ح خ،د  and other similar letters. This research uses the Classroom Action Research (CAR) method in one cycle, involving 15 children as research subjects.